Corporate Attributes and the Extent of Environmental Reporting: An Empirical Analysis of JSE-Listed Firms - Rudolph, Makhathini Lungani; Aliamutu, Kansilembo (Journal of Ecohumanism, 2025)
The study seeks to explore the impact of business attributes namely company size, firm age, leverage, and profitability, on environmental information disclosure by publicly listed firms in South Africa. This paper focuses on firm-level factors to improve understanding of how organisational attributes influence the extent and quality of environmental openness in a developing economy. It employs a quantitative research methodology that integrates empirical and statistical techniques to examine the relationship between corporate attributes and the extent of environmental reporting among firms listed on the Johannesburg Stock Exchange (JSE). The study covers a five-year period (2020–2024), chosen to illustrate the effects of South Africa's growing environmental regulations and the widespread implementation of integrated reporting following the enactment of the King IV Code of Corporate Governance. The model's overall significance (p = 0.000) demonstrates that firm-specific variables together affect environmental reporting behaviours. Profitability exhibits a robust positive and statistically significant correlation with environmental disclosure, indicating that financially stable companies are more inclined and capable of revealing sustainability information. Firm age shows a strong negative association, which means that younger organisations are more flexible, open, and sensitive to ESG trends than older, more established ones. The results also support both Voluntary Disclosure Theory (profitability-driven transparency) and parts of Institutional and Legitimacy Theories, which show that younger, more progressive companies are adapting to new reporting standards.